FORESTS AS A CENTER OF A GREEN ECONOMY - Wattimena, Cornelia Marietje Aneke (LPPM Univ. Ibn Khaldun Bogor, 2022)
The current use of forests should be directed more towards environmental services, absorbing air pollutants, tourism, and various faunal activities. A Green Economy is an economic regime that enhances human well-being and social equity, while significantly reducing environmental risks. Green Economy also means an economy that produces low or no carbon dioxide emissions and environmental pollution, saves natural resources, and is socially equitable. The community. of the State of Itawaka, East Saparua District, and Central Maluku Regency are mostly farmers, where daily activities have to go to the forest. so it is necessary to provide education about the importance of the forest not only to collect wood but also for other benefits such as: producing oxygen, environmental services, and as a green economy center. The solution offered to the people of Itawaka Country is in the form of counseling activities by providing education for the community to maintain and maintain the forest because the forest has various benefits that are not enjoyed by the current Itawaka community, it can be maintained for the enjoyment of the next generation. To realize a green economy, Indonesia needs to change its pattern of economic development from pursuing high economic growth to economic development that optimizes growth itself, because development that only pursues growth has brought social impacts on society in the form of poverty, economic and social inequality, and has an impact on declining quality. environment and biodiversity.